Development of Tax Teaching Materials: Withholding Tax - Tandy Sevendy; Nicholas Renaldo; Nyoto; Sudarno; Suhardjo; Harry Patuan Panjaitan; Marice Br Hutahuruk (First Ciera Publisher, 2023)
In order to ensure tax compliance and encourage transparency and efficiency in state revenue collection, the Indonesian government continues to make efforts to increase understanding and awareness regarding tax regulations among stakeholders. This research provides significant benefits for all participants and can be a first step in building a community of accountants who are more competent and skilled in dealing with the dynamics of taxation in this ever-evolving era. This research method is a literature study, analysis of learning needs, development of teaching materials, and evaluation of the effectiveness of the developed teaching materials. The conclusion of this study is the importance of a deep understanding of the rules and procedures related to Withholding Tax. In this context, accountants play a central role in assisting companies or their clients in fulfilling their tax obligations and avoiding administrative or criminal sanctions. It is hoped that accountants will have a better understanding of legal provisions, tax rates, withholding and reporting procedures, as well as recent changes in tax regulations regarding withholding tax.